Interval of irrigation suppression in beet cultivation under salt stress /Intervalo de supressao da irrigacao na cultura da beterraba sob estresse salino - Costa, Francisco H.R; de Azevedo, Benito M; de Sousa, Geocleber G; de Sousa, Leonardo V; Fernandes, Carlos N.V; de Pinto, Olienaide O.R; da Silva, Fred D.B; Canja, Juvenaldo F; Frazao, Diogo S (Revista brasileira de engenharia agrícola e ambiental, 2025)
Salt and water stresses affect the agronomic performance of the beet crop (Beta vulgaris L.). The aim of the present study was therefore to evaluate the effect of suppressing irrigation on the yield and quality of the tuberous root of beet under salt stress. The experiment was conducted from February to May 2023 in a greenhouse at the University of the International Integration of Afro-Brazilian Lusophony (UNILAB), Redencao, Ceara, Brazil. The experimental design used was completely randomized in a 5 * 2 factorial arrangement, with 5 repetitions, corresponding to five intervals of irrigation suppression: SI1 = no water suppression interval (control), SI2 = suppression interval from 20 to 35 days after sowing (DAS), SI3 = suppression interval from 35 to 50 DAS, SI4 = suppression interval from 50 to 65 DAS and SI5 = suppression interval from 65 to 80 DAS, and the two levels of electrical conductivity of the irrigation water: 0.8 and 6.2 dS [m.sup.-1]. The use of water with high salinity reduced the mass and length of the tuberous root, as well as its yield; however, it promoted an increase in the soluble solids content of beet. Salt stress negatively affected root diameter and pH in the water suppression intervals from 20 to 35 DAS and from 50 to 65 DAS. The treatment with water suppression interval from 35 to 50 DAS resulted lower performance in tuberous root mass and yield. Key words: Beta vulgaris L., salinity, water stress RESUMO: Os estresses salino e hidrico afetam o desempenho agronomico da cultura da beterraba (Beta vulgaris L.). Sendo assim, objetivou-se no presente estudo avaliar o efeito da supressao da irrigacao na produtividade e qualidade da raiz tuberosa da beterraba sob estresse salino. O experimento foi realizado de fevereiro a maio de 2023, em casa de vegetacao da Universidade da Integracao Internacional da Lusofonia Afro-Brasileira (UNILAB), Redencao, Ceara. O delineamento experimental utilizado foi o inteiramente casualizado (DIC) em arranjo fatorial 5 * 2, com 5 repeticoes, corresponde a cinco intervalos de supressoes de irrigacao: IS1 = sem intervalo de supressao de agua (testemunha), IS2 = intervalo de supressao dos 20 a 35 dias apos a semeadura (DAS), IS3 = intervalo de supressao dos 35 a 50 DAS, IS4 = intervalo de supressao dos 50 a 65 DAS e IS5 = intervalo de supressao dos 65 a 80 DAS e duas condutividades eletricas da agua de irrigacao: 0,8 e 6,2 dS [m.sup.-1]. O uso de agua com salinidade elevada reduziu a massa e o comprimento da raiz tuberosa, bem como a produtividade da raiz tuberosa; entretanto, promoveu aumento no teor de solidos soluveis da beterraba. O estresse salino afetou negativamente o diametro da raiz e o pH no intervalo de supressao de agua dos 20 a 35 DAS e dos 50 a 65 DAS. O tratamento com intervalo de supressao de agua dos 35 a 50 DAS, proporciona menor desempenho em massa de raiz tuberosa e a producao da beterraba. Palavras-chave: Beta vulgaris L., salinidade, estresse hidrico